Uppkomsten av ett professionellt medicinskt fält Läkares, sjuksköterskors och laboratorieassistenters formering - Carlhed Ydhag, Carina (Stockholm Studies in Education, 2020)
The book deals with the rise of the professional medical field in Sweden during Middle Ages to 1990s with special focus on the professions which have been active in the field, doctors, nurses and biomedical analysts (previous laboratory assistants). Often books about professions focus on one profession or one important institution but there are none covering the wider professional medical field over time.;The analysis of the professional field departs from acknowledging the social processes which are profound in the development of professional knowledge, power and social order. Why has the medical profession such high status? How come that certain professions have powers over others? What kind of professional knowledge does the medical science contribute with? These are some of the questions this book is aiming to answer, using theory from the tradition of sociology of professions. ;The book gives an overview of the development of the Swedish state and the healthcare system in particular. In addition, it analyses how early organizational traditions, social mobilization and the creation of a common cognitive base both stimulate and limit opportunities for occupations and their professionalization within the field. It contributes to a deepened knowledge about professions which extends the everyday meaning of an occupation. Potential readers are researchers within sociology of professions, university students and professionals within the medical field who have interest in professions and power structures.